The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/1678-9199-jvatitd-2020-0043
|View full text |Cite
|
Sign up to set email alerts
|

Envenomation by Trimeresurus stejnegeri stejnegeri: clinical manifestations, treatment and associated factors for wound necrosis

Abstract: Background: Trimeresurus stejnegeri stejnegeri bite induces tissue swelling, pain, thrombocytopenia, rhabdomyolysis, and acute renal failure. However, the incidence of coagulopathy, factors associated with wound necrosis, and the appropriate management of this condition have not been well characterized yet. Materials: This study included patients bitten by T . s . stejnegeri … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 47 publications
(73 reference statements)
1
23
0
Order By: Relevance
“…morganii are frequently present in the infected bite wound [ 21 ]. Mao et al and Chiang et al suggested that first-generation cephalosporin with aminoglycoside or sulfamethoxazole/trimethoprim is the preferable antibiotics in the management of infected Protobothrops mucrosquamatus and Trimeresurus stejnegeri stejnegeri bites [ 22 , 23 ]. These suggestions are based on conventional wound microbial culture without prior determination of antibiotic administration before obtaining cultures, thus rendering these suggestions biased.…”
Section: Discussionmentioning
confidence: 99%
“…morganii are frequently present in the infected bite wound [ 21 ]. Mao et al and Chiang et al suggested that first-generation cephalosporin with aminoglycoside or sulfamethoxazole/trimethoprim is the preferable antibiotics in the management of infected Protobothrops mucrosquamatus and Trimeresurus stejnegeri stejnegeri bites [ 22 , 23 ]. These suggestions are based on conventional wound microbial culture without prior determination of antibiotic administration before obtaining cultures, thus rendering these suggestions biased.…”
Section: Discussionmentioning
confidence: 99%
“…s . stejnegeri bites; both studies were analyzed using multivariate logistic regression [ 25 ]. Another study has found risk factors of ecchymosis and cyanosis in rattlesnake bites in North America, analyzed as relative risk assessment [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…atra has distinct biological features that makes visual identification relatively easy [6,24]. The clinical manifestations caused by N. atra envenoming, however, overlap with those of the common crotaline snakebites [11,14,25]. Therefore, in this study we only included patients with a definite diagnosis and those who saw the culprit snake to construct the surgical risk score and excluded those with snakebites for which the culprit snake could not be identified (i.e., clinical diagnosis [4]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations